[Elephant Seals on Beach] - Streng, Evelyn Fiedler (1999)
Photograph of elephant seals and a group along a brown beach. The beach wraps around the blue ocean to the right, lined by a rocky cliff that is visible in the background. Groups of people stand in brown bushes along hills at the bottom of the photograph. A line of elephant seals lay along the brown beach in the bottom left corner of the photograph.